Risk Factors for the Development of an Incisional Hernia after Sigmoid Resection for Diverticulitis: An Analysis of 33 Patient, Operative and Disease-associated Factors. Issue 5 (May 2015) - Connelly, Tara M.; Tappouni, Rafel; Mathew, Paul; Salgado, Javier; Messaris, Evangelos
Incisional hernia (IH) is a relatively common sequelae of sigmoidectomy for diverticulitis. The aim of this study was to investigate factors that may predict IH in diverticulitis patients. Two hundred and one diverticulitis patients undergoing sigmoidectomy between January 2002 and December 2012 were identified (mean follow-up 5.15 ± 2.33 years). Patients with wound infections were excluded. Thirteen patient-associated, three diverticular disease-related, and 17 operative variables were evaluated in patients with and without IH. Volumetric fat was measured on pre-operative CTs. Fischer's exact, χ 2, and Mann–Whitney tests and multivariate regression analysis were used for statistics. Thirty-four (17%) patients had an IH. On multivariate analysis, wound packing (OR 3.4, P = 0.017), postoperative nonwound infection (OR 7.4, P = 0.014), and previous hernia (OR 3.6, P = 0.005) were as independent predictors of IH. Fifteen of 34 (44%) patients who developed a hernia had a history of prior hernia. Of 33 potential risk factors analyzed, including smoking, chronic obstructive pulmonary disease, and obesity, the only patient factor present preoperatively associated with increased risk of a postsigmoidectomy hernia after multivariate analysis was a history of a previous hernia. Preoperative identification of patients with a history of hernia offers the opportunity to employ measures to decrease the likelihood of IH.